'Young versus Old' or Intergenerational Solidarity. Issue 2 (June 2013) - Laborde, Jean-Pierre
This contribution enters into the ageing debate through the perspective of intergenerational solidarity. Far away from the age struggle and the age discrimination issue, contemporary French Labour Law is in favour of age cooperation and is perhaps developing a trend of going beyond the consideration of age. In light of this, it is examined, in this contribution, what overcoming the age issue can or cannot mean.